Intraoperative Anaphylaxis to the Bovine Flowable Gelatin Matrix: A Report of 2 Cases. Issue 1 (3rd January 2022) - Coury, Josephine R.; Skaggs, Kira F.; Marciano, Gerard F.; Pinyavat, Teeda; Naseef, Mervat; Roye, Benjamin D.; Vitale, Michael G.
Abstract : Case: We present 2 cases of life-threatening intraoperative anaphylaxis to the bovine flowable gelatin matrix during pediatric spinal deformity surgery for kyphoscoliosis. Both patients had no known bovine or gelatin allergies. Anaphylaxis occurred shortly after pressurized injection into the first cannulated pedicle tract and was successfully treated with epinephrine, diphenhydramine, and methylprednisolone infusion. The allergic reaction was confirmed with tryptase levels and serum-specific immunoglobulin E for beef, pork, bovine collagen, and porcine collagen. Conclusion: In patients with beef, pork, or gelatin intolerance, a significant atopic history or childhood vaccine reaction, preoperative allergy consultation, and testing should be performed to prevent this life-threatening complication.